WATER CONTAMINATION ASSOCIATED WITH THE USE OF RUDIMENTARY SEPTIC PITS: STATISTICAL ANALYSIS OF WATER QUALITY DATA IN ITIQUIRA-MT (2019–2023) - Lima, Evaí Pereira da Silva; Pereira, Aires José (Seven Editora, 2025)
This study analyzes the impacts of rudimentary cesspit use on the quality of water intended for human consumption in the municipality of Itiquira–MT, based on data collected by environmental surveillance between 2019 and 2023. A total of 547 water sample results were evaluated, considering the parameters free residual chlorine, turbidity, pH, total coliforms, and Escherichia coli. Data were statistically processed using Jamovi software, allowing identification of temporal and spatial contamination patterns. Results indicated a recurrent presence of E. coli, peaking in 2021 (24.6% of samples). It is concluded that rudimentary cesspits significantly contribute to water contamination, reinforcing the need for public sanitation policies and preventive actions.DOI: https://doi.org/10.56238/sevened2025.036-044